Ownership Structures within Hungarian Family Businesses – Theories and Practice - Tobak, Júlia (Applied Studies in Agribusiness and Commerce, 2018)
We can talk about family business if the notions of family, ownership and business are closely connected to each other, namely if the business is in the possession of the family, managed and controlled by the family members. A family owned company is a business where a family has the majority ownership and/or the majority management and at least one family member actively works in the firm, the family owns the business. The study contains the results of research on ownership structure of family owned businesses. The examined family businesses are interested in longterm preservation of values, thus succession of generations plays a key role in their case. They attaches great importance how the ownership structure develops. The methotology to know more about the ownership structure of family businesses 11 expert interviews were made between november 2016 and september 2017 with owners and next generations of family owned agri-food enterprises in Hungary. A case study has been prepared too in this topic with the participation of companies with different activities (production, service, trade). In order to classify the analysed companies six categories of ownership were developed. These are non-owner, emotional owner, partial owner, controlling owner, majority owner and exclusive/ sole owner. Each generation of the analysed FBs were classified to these categories. According to the results the analysed family owned companies even are sharing the property within family. There are only two interviewed companies whose case we can talk about exclusive/sole ownership.JEL Classification: G32